2018
DOI: 10.1002/btpr.2672
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and catalytic properties of protease from Bacillus sp. P45 active in organic solvents and ionic liquid

Abstract: The parameters half-life, z value, enthalpy, entropy, and free energy were evaluated in the temperature range of 40 to 55°C for a Bacillus sp. P45 protease present in a medium composed of ionic liquid (IL) and organic solvent. The protease was previously treated in IL [Emim][Tf N] and increased activity was observed in four out of five organic solvents tested. The reaction medium containing acetone and IL (1:1 v/v ratio) was more stable than the buffer medium, with half-life of 2.4 h at 55°C. Thermodynamic par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Arrhenius plots of S. carnosus RT6 protease (Figure 3b) indicated that the calculated activation energy ( E a ) was about 24.62 kJ/mol (Table 2), the activation energy was lower than those of other studied, such as Aspergillus fumigatus protease (62 kJ/mol) (Hernández‐Martínez et al., 2011) and Bacillus sp. P45 protease (92.7 kJ/mol) (de Borba et al., 2018), and was higher than that of B. stearothermophilus alkaline protease (17.31 kJ/mol) (Abdel‐Naby et al., 2017). A low E a value was beneficial to the formation of enzyme–substrate complex and therefore required less energy (Abdel‐Naby et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Arrhenius plots of S. carnosus RT6 protease (Figure 3b) indicated that the calculated activation energy ( E a ) was about 24.62 kJ/mol (Table 2), the activation energy was lower than those of other studied, such as Aspergillus fumigatus protease (62 kJ/mol) (Hernández‐Martínez et al., 2011) and Bacillus sp. P45 protease (92.7 kJ/mol) (de Borba et al., 2018), and was higher than that of B. stearothermophilus alkaline protease (17.31 kJ/mol) (Abdel‐Naby et al., 2017). A low E a value was beneficial to the formation of enzyme–substrate complex and therefore required less energy (Abdel‐Naby et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…This confirms that the change in the ∆G # d is the energy barrier for the enzyme deactivation. The higher the ∆G # d is, the more stable the enzyme [27,35]. The increase in the stability of horseradish peroxidase immobilized on the membrane relative to native horseradish peroxidase is accompanied by a decrease of ∆H # and ∆S # values according to an enthalpy-entropy [34].…”
Section: The Values Of Thermodynamic Parameters Of Active and Deactiv...mentioning
confidence: 99%
“…have stabilizing effects even at high concentrations or dosages [68][69][70]. Metabolization of acetone by carboxylation to acetoacetate has been demonstrated in aerobic and anaerobic bacteria [71,72].…”
Section: Plos Onementioning
confidence: 99%